2023
DOI: 10.5397/cise.2022.00948
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of clinical tests to rule out elbow fracture: a systematic review

Abstract: Background: Elbow traumas represent a relatively common condition in clinical practice. However, there is a lack of evidence regarding the most accurate tests for screening these potentially serious conditions and excluding elbow fractures. The purpose of this investigation was to analyze the literature concerning the diagnostic accuracy of clinical tests for the detection or exclusion of suspected elbow fractures.Methods: A systematic review was performed using the Preferred Reporting Items for a Systematic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This systematic review 8 found several clinical tests for the evaluation of elbow fracture to be useful. The studies included in the systematic review were performed in the emergency department setting, and all tests are easy to perform and reproducible, making them important components of the evaluation particularly in settings where imaging is not readily available.…”
Section: Caveatsmentioning
confidence: 99%
See 4 more Smart Citations
“…This systematic review 8 found several clinical tests for the evaluation of elbow fracture to be useful. The studies included in the systematic review were performed in the emergency department setting, and all tests are easy to perform and reproducible, making them important components of the evaluation particularly in settings where imaging is not readily available.…”
Section: Caveatsmentioning
confidence: 99%
“…Five studies evaluated diagnostic accuracy of index tests in patients > 16 years, and seven in patients < 14–16 years. Physicians or nurses performed tests in all studies, and most studies did not provide training on how to perform the clinical tests 8 . The quality of the included trials was assessed with the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS‐2) checklist.…”
Section: Narrativementioning
confidence: 99%
See 3 more Smart Citations